Government role in development of child-friendly city based on traditional games - Genggong, Marsia Sumule; Ashmarita, - (International Research Journal of Management, IT & Social Sciences (IRJMIS), 2018)
The purpose of this study is to synergize and integrate theoretical-conceptual with the development of a child-friendly city (CFC) related to the community, local elites and the government of Kendari city. It is also intended to explore the values that exist in childrens traditional games in the area of Kendari city with the empirical reality that occurs during the process of urban development. This research is descriptive qualitative. Data collection technique used in-depth interviews and field observations. The results show that childrens traditional games in Kendari city today tend to experience a shift towards modern games based on computer and television technology. This condition affects the behavior and character of children. Children easily give up, unable to cooperate, difficult to interact with the environment are some negative impact of the modern games. Support and cooperation from various parties are needed to overcome this problem. Development of CFC is a government priority program. The CFC provides guarantees for the fulfillment of the children rights. To realize a CFC, the government should prepare the childrens creative space, cooperate with the relevant parties, and form a task force for CFC. The results of the research can be used as a recommendation in the form of regulations and policies of Kendari city government toward the development of CFC through childrens traditional games approach.